KONSEP DETERMINISME DALAM FILM SOUL (STUDI ANALISIS SEMIOTIKA ROLAND BARTHES) - Arni Arni (Program Studi Ilmu Komunikasi FISIP UM Buton, 2023)
Abstract Soul is a film directed by Pate Doctor. The film's story is about the concept of determinism, whose core idea is a causal relationship (causal). It means everything that happens to us is determined by pre-existing causes, such as talent, personality, spirit, and desire. These pre-existing causes have been determined before humans are born. They became the guide to prevent individuals from deviating from his/her destiny. This study aims to analyze the meaning of determinism's message in the film Soul, using Roland Barthes' semiotic analysis. The research method used is a qualitative paradigm with a descriptive research type. Qualitative research aims to explain the denotative signs, connotations, and myths in the film Soul. The data analysis technique uses Roland Barthes' semiotic analysis to develop a more dynamic signified-dichotomous model. The results of the research show that 1. The thesis or the big idea of this film is that everything that happens to us has sufficient reasons why it happens; 2. Personality and spark formed in Your seminars are not the purpose but something that ignites and encourages the soul to do what is determined initially. However, the condition does not limit the soul if it wants to escape its predetermined purpose. 3. A person who can recognize his passion from the start is unlikely to take the wrong path or the path of another. Keywords: Determinism; Soul Movies; Semiotics